Assessing the optimal preparation strategy to minimize the variability of cardiac pyruvate dehydrogenase flux measurements with hyperpolarized MRS. (24th July 2018) - Timm, Kerstin N.; Apps, Andrew; Miller, Jack J.; Ball, Vicky; Chong, Cher‐Rin; Dodd, Michael S.; Tyler, Damian J.
Abstract : Hyperpolarized [1‐ 13 C] pyruvate MRS can measure cardiac pyruvate dehydrogenase (PDH) flux in vivo through 13 C‐label incorporation into bicarbonate. Using this technology, substrate availability as well as pathology have been shown to modulate PDH flux. Clinical protocols attempt to standardize PDH flux with oral glucose loading prior to scanning, while rodents in preclinical studies are usually scanned in the fed state. We aimed to establish which strategy was optimal to maximize PDH flux and minimize its variability in both control and Type II diabetic rats, without affecting the pathological variation being assessed. We found similar variances in the bicarbonate to pyruvate ratio, reflecting PDH flux, in fed and fasted/glucose‐loaded animals, which showed no statistically significant differences. Furthermore, fasting/glucose loading did not alter the low PDH flux seen in Type II diabetic rats. Overall this suggests that preclinical cardiac hyperpolarized magnetic resonance studies could be performed either in the fed or in the fasted/glucose‐loaded state. Centres planning to start new clinical studies with cardiac hyperpolarized magnetic resonance in man may find it beneficial to run small proof‐of‐concept trials to determine whether metabolic standardizations by oral or intravenous glucose load are beneficial compared with scanning patients in the fed state. Abstract : Hyperpolarized [1‐ 13 C] pyruvate MRS can measure cardiac pyruvate dehydrogenase (PDH) flux in vivo through 13 C‐label incorporation into bicarbonate. We aimed to establish if ad libitum feeding or overnight fasting followed by an intravenous glucose bolus is optimal to maximize PDH flux and minimize its variability in both control and Type II diabetic rats, without affecting the pathological variation being assessed. We found similar variances in both fed and glucose‐loaded animals, which showed no statistically significant differences.